Lung Transplantation With Donation After Circulatory Determination of Death Donors and the Impact of Ex Vivo Lung Perfusion. Issue 4 (13th March 2015) - Machuca, T. N.; Mercier, O.; Collaud, S.; Tikkanen, J.; Krueger, T.; Yeung, J. C.; Chen, M.; Azad, S.; Singer, L.; Yasufuku, K.; de Perrot, M.; Pierre, A.; et al.
Abstract : The growing demand for suitable lungs for transplantation drives the quest for alternative strategies to expand the donor pool. The aim of this study is to evaluate the outcomes of lung transplantation (LTx) with donation after circulatory determination of death (DCDD) and the impact of selective ex vivo lung perfusion (EVLP). From 2007 to 2013, 673 LTx were performed, with 62 (9.2%) of them using DCDDs (seven bridged cases). Cases bridged with mechanical ventilation/extracorporeal life support were excluded. From 55 DCDDs, 28 (51%) underwent EVLP. Outcomes for LTx using DCDDs and donation after neurological determination of death (DNDD) donors were similar, with 1 and 5‐year survivals of 85% and 54% versus 86% and 62%, respectively (p = 0.43). Although comparison of survival curves between DCDD + EVLP versus DCDD‐no EVLP showed no significant difference, DCDD + EVLP cases presented shorter hospital stay (median 18 vs. 23 days, p = 0.047) and a trend toward shorter length of mechanical ventilation (2 vs. 3 days, p = 0.059). DCDDs represent a valuable source of lungs for transplantation, providing similar results to DNDDs. EVLP seems an important technique in the armamentarium to safely increase lung utilization from DCDDs; however, further studies are necessary to better define the role of EVLP in this context. Abstract : This study describes the experience of the Toronto Lung Transplant Program with lung transplantation using controlled donation after determination of circulatory arrest donors, with special focus on the current role of ex vivo lung perfusion in this particular scenario. See editorial by Snell et al on page859 .